Pattern of vitamin D status in prediabetic individuals: a case control study at tertiary hospital in South India - K. M., Srinath; K. C., Shashidhara; G., Rajeev Reddy; Basavegowda, Madhu; Debnath, Kishaloy; M.G., Mahesh (International Journal of Research in Medical Sciences, 2016)
Background: Role of vitamin D in the regulation of calcium metabolism is well established. Vitamin D deficiency has been linked to impaired glucose tolerance and type 2 DM in humans. There is a limited available data on the relationship of vitamin D insufficiency/deficiency with glucose homeostasis among prediabetic individuals in South Indian population. Hence we examined serum 25(OH) D3 concentration among prediabetics. The objective of this study is to evaluate prevalence of vitamin D deficiency in prediabetics and to study any correlation between vitamin D and BMI, FBS and PPBS among prediabetics. Methods: A case control study was carried out among 40 prediabetics & controls, after obtaining consent from subjects and clearance from institutional ethics committee. Serum vitamin D levels were measured by radioimmunoassay in both groups. Statistical analysis was done using “t” test & Pearson correlation co-efficient (r). Results: Vitamin D levels less than 20 ng/ml were found in 72.5% of cases and 35% of controls. 5% of the cases and 12.5% of the controls had vitamin D above 30 ng/ml and this difference was statistically significant. Mean vitamin D levels in cases and controls was 17.09±5.89 ng/ml and 23.67±11.02 ng/ml respectively (P<0.05). A significant inverse correlation was observed between vitamin D levels & body mass index (r=-0.274; p=0.014); random blood sugar (r=-0.35; p=0.001); fasting blood sugar (r=-0.328; p=0.003); post prandial blood sugar (r=-0.276; p=0.013). Conclusions: High prevalence of hypovitaminosis D exists among prediabetics and there is significant inverse correlation between BMI, FBS, PPBS and vitamin D levels. Hence, a prospective study covering large pre-diabetic individuals is essential to confirm the findings.